Colombian agriculture: approaching agriculture 4.0 - Montoya Alvarez, Yeimy Andrea; Rodríguez Molano, José Ignacio; Contreras Bravo, Leonardo Emiro (Ingeniería Solidaria, 2022)
Introduction: This article is the product of the research “Agriculture 4.0 in Colombia” developed at the Universidad Distrital Francisco José de Caldas over a three-year observation window: 2019, 2020 and part of 2021. Here, we present some of the most relevant aspects related to the technological development of Colombian agriculture and of projects that have been carried out in the country in the field of precision agriculture. It also addresses the context of the progress of Agriculture 4.0 at the national level and presents possible IoT integration tools and architectures applicable in this field. Finally, the benefits and implications of the development of Agriculture 4.0 in the country are highlighted, concluding that its consolidation is necessary to strengthen national agricultural development.Methodology: A review of information on precision agriculture and Agriculture 4.0 in Colombia was carried out, covering scientific articles from databases such as IEEE Explore, Scopus and Elsevier, and official documents from governmental websites.Results: The development of Agriculture 4.0 in Colombia has not yet been fully explored, however, research and pilot projects have been carried out on Agriculture 4.0 in the national territory.Conclusions: To strengthen the deployment of Agriculture 4.0 in Colombia, it is necessary to invest in technology, provide education and training, promote research, and adopt modern technological practices in agricultural activities.Originality: The context of the development of Agriculture 4.0 in Colombia in terms of projects and research is presented, as well as some IoT integration architectures and tools applicable in Colombian agriculture.
Keywords: agriculture 4.0; architectures; automation; crop; precision agriculture